2021
DOI: 10.1177/2399808320985843
|View full text |Cite
|
Sign up to set email alerts
|

Spatial sensitivity analysis for urban hotspots using cell phone traces

Abstract: Urban hotspots can be used to model the structure of urban environments and to study or predict various aspects of urban life. An increasing interest in the analysis of urban hotspots has been triggered by the emergence of pervasive technologies that produce massive amounts of spatio-temporal data including cell phone traces (or Call Detail Records). Although hotspot analyses using cell phone traces are extensive, there is no consensus among researchers about the process followed to compute them in terms of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Hotspots or high-traffic communication areas [21] have a high activity and density compared to the other areas in a smart city [22]. Hotspot analysis is a classical problem concerned with spatial analysis [23]. Telecommunication operators and companies always care to identify the hotspots in a city to improve the quality of service.…”
Section: Problem Statementmentioning
confidence: 99%
“…Hotspots or high-traffic communication areas [21] have a high activity and density compared to the other areas in a smart city [22]. Hotspot analysis is a classical problem concerned with spatial analysis [23]. Telecommunication operators and companies always care to identify the hotspots in a city to improve the quality of service.…”
Section: Problem Statementmentioning
confidence: 99%
“…Kadar and Pletikosa extracted footfall from checkins, subway and taxi data, along with other census and POI features, to predict the number of crimes for a given census tract in the next year [25]; De Nedai et al proposed a spatially filtered Bayesian Negative Binomial model to study how social, built environment and footfall influence criminal activity [16]; Rumi et al proposed a set of footfall dynamic features computed from Foursquare check-ins including visitor count, visitor entropy and homegeneity or region popularity, and showed that these features improved the performance of short-term crime prediction for certain types of crime with F1-score increases of up to 2% [38]; and Stec et al showed that deep learning architectures that use footfall from public transit, together with weather conditions that have been reported to affect crime, enhance the accuracy of crime predictions [40]. In addition to footfall, Wu et al quantified urban spatial structure using human mobility to predict number of crimes for municipalities in the next year [49,50].…”
Section: Modeling Crime With Human Mobilitymentioning
confidence: 99%
“…Another mobility feature used in crime prediction contexts is the origin-destination matrix (OD) that characterizes human mobility (flows) between census tracts. Human mobility data has been used to characterize human behaviors in the built environment [23][24][25][26][27], for public safety [10,14], during epidemics and disasters [28][29][30][31][32][33][34][35], as well as to support decision making for socio-economic development [36][37][38][39][40][41]. In this paper, we will focus on deep learning crime prediction models that exploit the predictive power past crime data and OD mobility matrices [10].…”
Section: Crime Prediction With Mobility Patternsmentioning
confidence: 99%